Boosting loading capacities of shapeable metal–organic framework coatings by closing the interparticle spaces of stacked nanocrystals. Issue 50 (5th June 2019) - Wei, Songbo; Liu, Yan; Zheng, Jiating; Huang, Siming; Chen, Guosheng; Zhu, Fang; Zheng, Juan; Xu, Jianqiao; Ouyang, Gangfeng
Abstract : Herein, an intriguing strategy is presented for preparing monolithic metal–organic framework coatings through compactly filling up the interparticle spaces in the stacked architectures of nanocrystals. Abstract : Herein, an intriguing strategy is presented for preparing monolithic metal–organic framework (MOF) coatings through compactly filling up the interparticle spaces in the stacked architectures of nanocrystals. The monolithic coatings exhibited remarkably enhanced performance (double to triple compared to the MOF powders) for analyte extraction, due to the increased volumetric BET areas.